Polymorphism of metal-organic frameworks: direct comparison of structures and theoretical N2-uptake of topological - and -isomers. - Schmitt, Wolfgang; Zhu, Nian-Yong (My University, 2014)
The syntheses, calculated surface areas and N2 uptakes of two highly augmented {Cu}2 `paddlewheel?-based MOFs provide a direct comparison of tbo and pto framework polymorphs with identical composition.
PUBLISHED
Keywords: Chemistry